The Arabic Program Planning Management in Modern Islamic Boarding School Al Kautsar Banyuwangi - Irnaini Al Badri, Hakiki Rikza; Pritasari, Shofie Asya; Maisarah, Imas; Kholid, Nur (Jurusan Pendidikan Bahasa Arab, 2025)
From time to time, the Arabic language has received more and more attention, so that currently Arabic can be learned through formal and non-formal education. Modern Islamic Boarding School Al Kautsar Banyuwangi is one of the Islamic education institutions that makes the Arabic language program one of the main icons of its institution. The success of a program can be seen from whether the management is running well or not, especially at the planning stage. During the planning stage there are a lot of things that need to be considered, one of which is the problems that might occur. This study aims to reveal how to plan an Arabic language program in terms of the approach and scope of planning carried out at the Modern Islamic Boarding School Al Kautsar Banyuwangi and the problems it faces. This study uses descriptive qualitative research methods with data collected through interviews and observations. The result is that the Arabic language program at Modern Islamic Boarding School Al Kautsar Banyuwangi uses two planning models and a 7-step planning process which includes three interrelated dimensions. The problems experienced occurred in terms of human resources, namely the limited number of ustadz and ustadzah, several persons in charge of activities who were not qualified in this field, and lack of management knowledge, lack of time and fear of failure.